Asia : A Survey of Gender Budgeting Efforts - Chakraborty, Lekha (Washington, D.C. : International Monetary Fund, 2016)
This paper reviews gender budgeting efforts in Asia. The countries in the region have achieved mixed success in improving gender equality. Gender budgeting is ideally a fiscal innovation that translates gender-related goals into budgetary commitments and can help countries to achieve the Sustainable Development Goals with regard to gender equality. India has a sustainable gender budgeting model for the region, while a few countries in the region have begun such efforts more recently. The legislative mandates for gender budgeting in the Philippines and South Korea are remarkable achievements and are contributing to their efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet